Cold-Hardiness Strategies of Invertebrates - Gulevsky, A. K.; Relina, L. I. (Problems of Cryobiology and Cryomedicine, 2024)
The review is devoted to the classification of invertebrates’ cold-hardiness types. Classically distinguished strategies of cold-hardiness and their biochemical mechanisms are considered in the research, as well as the data of research results requiring new approaches to invertebrates’ cold-hardiness classification are discussed.